Increased CSF aquaporin-4, and interleukin-6 levels in dogs with idiopathic communicating internal hydrocephalus and a decrease after ventriculo-peritoneal shunting - Schmidt, Martin J.; Rummel, Christoph; Hauer, Jessica; Kolecka, Malgorzata; Ondreka, Nele; McClure, Vanessa; Roth, Joachim; Justus Liebig University Giessen (My University, 2016)
Background: Studies in animal models, in which internal hydrocephalus has been induced by obstructing the cerebrospinal fluid pathways, have documented an up-regulation of the concentrations of aquaporin-4 (AQP4) in the brain. In this study, the concentrations of aquaporin-1 (AQP1), AQP1, AQP4 and interleukin-6 (IL-6) were determined in the CSF of dogs with idiopathic communicating hydrocephalus before and after the reduction of intraventricular volume following ventriculo-peritoneal shunt (VP-shunt) treatment. Results: The concentrations of AQP4 and IL-6 were increased in the cerebrospinal fluid of dogs with hydrocephalus compared to controls. Both parameters significantly decreased after surgical treatment, accompanied by decrease of ventricular size and the clinical recovery of the dogs. AQP1 was not detectable in CSF. Conclusions: Brain AQP4 up-regulation might be a compensatory response in dogs with hydrocephalus. Future determination of AQP4 at the mRNA and protein level in brain tissue is warranted to substantiate this hypothesis.
Keywords: Aquaporin; Communicating hydrocephalus; Dogs; Interleukin-6; ddc:630